Radically Embodied Compassion Training: Cultivating Psychotherapist Courage, Distress Tolerance and Compassionate Responsiveness via Traditional Martial Arts - Clapton, Neil; Hiskey, Syd (Advances in Social Sciences Research Journal, 2024)
Psychotherapeutic encounters inevitably entail moments and episodes of disaffiliation, ruptures and conflict. These events can pose significant challenges and threats to both client and therapist. Resolving and repairing such ruptures requires therapists to tolerate not only their clients’ but also their own distress, to better afford the courage and wisdom to respond compassionately. Whilst there is plenty of excellent research and guidance on how to respond to and repair alliance ruptures, few approaches explicitly focus on the development of the underlying (neuro)physiological capacities, embodied motivational switching abilities and somatic resources to be able to do so in situations of high relational threat. Traditional martial arts provide a powerful and fruitful means to entrain these competencies and processes, which can feasibly be transferred to psychotherapeutic encounters. This paper outlines the development of training workshops for therapists/clinicians based on traditional martial arts principles and practices, embodied neuroscience and interpersonal neurobiology. This overview will thus help illuminate how such training may afford therapists/clinicians greater distress tolerance and compassionate responsiveness, otherwise termed Radically Embodied Compassion (Clapton & Hiskey, 2020), in difficult therapeutic encounters such as alliance ruptures.